Nasal resonance changes after endoscopic endonasal transsphenoidal skull base surgery: Analysis of voice quality. Issue 6 (19th November 2021) - Kasemsiri, Pornthep; Duangthongphon, Pichayen; Prathanee, Benjamas; Thongrong, Cattleya
Abstract: Objectives: To study the effect of endoscopic endonasal transsphenoidal surgery on voice quality in patients with pituitary lesions. Methods: An observational study comparing voice quality before and after surgery was conducted between September 2015 and September 2017 at Srinagarind Hospital, Khon Kaen University, Thailand. Pituitary tumor patients who underwent endoscopic endonasal transsphenoidal surgery were recruited. The nasal corridors were created with a type I (preserving both middle turbinates with a rescue flap) or type II (cutting one middle turbinate with a raised nasoseptal flap) for the binostril with four‐hand technique. All patients were evaluated for nasal resonance, acoustic parameters, acoustic perception, and self‐assessment of their satisfaction with postoperative voice changes with a visual analog scale (VAS). The patients were evaluated 1 day before surgery and at 1 and 3 months after surgery. Results: Forty‐four patients, including 19 males and 25 females with a mean age of 50.0 ± 15.6 years, were enrolled. Mean scores for nasal resonance and all acoustic parameters were not significantly changed after surgery for either nasal corridor type ( p  > .05). Regarding acoustic perception, word and sentence and GIRBAS scores showed no significant difference before and after surgery ( p  > .09) in either type of nasal corridor. There was no incidence of hypernasality voice after surgery. Patients' self‐satisfaction ratings (i.e., VAS) with voice quality were high and showed no significant change 1 and 3 months postsurgery ( p  > .05). Conclusions: These endoscopic endonasal transsphenoidal approaches are minimally invasive skull base surgery techniques that have minimal effects on postsurgery voice quality. Trial Registration: This trial was registered at ClinicalTrial.gov (NCT02828514). Level of Evidence: 4.